Sejarah Madzhab Qira’at Ashim Riwayat Hafs Di Nusantara; Tinjauan Historis Kritis - Malik, Muhammad Abdul (STAI Darul Kamal NW Kembang Kerang, 2022)
Various readings (qira'at) of the Qur'an have existed since it was revealed to the Prophet Muhammad in Mecca. However, this recitation began to be used when the Prophet was in Medina. When delivering the revelations he had received, the prophet always used readings that suited the abilities of the companions present at that time. So that the companion's ability in reciting the Qur'an also varies, depending on how many types of recitation (qira'at) he has received from the Messenger of Allah. As a result, the variety of qira'at that developed in each region experienced differences. After the death of the Prophet, the companions became more and more active in spreading the Qur'an by establishing madrasahs around where they lived. So, it is not surprising when after a generation of companions, qira'at experts appeared among tabi'in, one of them: Madzhab qira'at Ashim's narration of Hafsh which is qira'at or reading used to read the Qur'an in the archipelago.